Cardioprotection via mitochondrial transplantation supports fatty acid metabolism in ischemia-reperfusion injured rat heart - Jang, Jehee; Kang, Ki-Woon; Kim, Young-Won; Jeong, Seohyun; Park, Jaeyoon; Park, Jihoon; Moon, Jisung; Jang, Junghyun; Kim, Seohyeon; Kim, Sunghun; Cho, Sungjoo; Lee, Yurim; et al. (The Korean journal of physiology & pharmacology, 2024)
In addition to cellular damage, ischemia-reperfusion (IR) injury induces substantial damage to the mitochondria and endoplasmic reticulum. In this study, we sought to determine whether impaired mitochondrial function owing to IR could be restored by transplanting mitochondria into the heart under ex vivo IR states. Additionally, we aimed to provide preliminary results to inform therapeutic options for ischemic heart disease (IHD). Healthy mitochondria isolated from autologous gluteus maximus muscle were transplanted into the hearts of Sprague-Dawley rats damaged by IR using the Langendorff system, and the heart rate and oxygen consumption capacity of the mitochondria were measured to confirm whether heart function was restored. In addition, relative expression levels were measured to identify the genes related to IR injury. Mitochondrial oxygen consumption capacity was found to be lower in the IR group than in the group that underwent mitochondrial transplantation after IR injury (p < 0.05), and the control group showed a tendency toward increased oxygen consumption capacity compared with the IR group. Among the genes related to fatty acid metabolism, (p < 0.05) and (p < 0.01) showed significant expression in the following order: IR group, IR + transplantation group, and control group. These results suggest that mitochondrial transplantation protects the heart from IR damage and may be feasible as a therapeutic option for IHD.